The Impact of Electronic Medical Records on Hospital Revenue from INA-CBGs Claims - Warsi Maryati; Anton Susanto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Incorrect diagnosis and procedure coding are the major factors which lead to substantial reductions of claims in the INA-CBGs system. Studies have indicated reported losses of up to 23% due to this alone. This paper discusses whether Electronic Medical Records, hereafter referred to as EMRs, will mitigate such financial risks through improved documentation and coding quality. The study is a cross-sectional analysis based on 100 INA-CBGs inpatient claim documents, 50 with the use of EMRs and another 50 with the use of manual records, selected by simple random sampling technique. Five key variables have been related using the Chi-square test, multiple logistic regression analysis, and Structural Equation Modeling (SEM). Of all claims analyzed in this study, only 55% had complete medical information; diagnosis codes were accurate in 66% of them while accurate procedure codes accounted for just about 48%. Hospitals where EMRs are used had less revenue reduction at IDR 119,444,050 or -23.47%, compared to hospitals without EMRs which used manual records with a revenue reduction rate standing at IDR 272,422,069 or -47.92%. Of the claims analyzed, 55% had complete medical information, 66% had accurate diagnosis codes, and 48% had accurate procedure codes. Hospitals using EMRs experienced a smaller revenue reduction (IDR 119,444,050 or -23.47%) compared to those using manual records (IDR 272,422,069 or -47.92%). Diagnosis codes at accuracy (b = 3.595; p = 0.001), procedure codes at accuracy (b = 4.461; p < 0.001), documentation at completeness (b = 2.331; p < 0.001) and EMR use (b = 0.425; p < 0.001) were all significant factors with results of claims. EMRs significantly improve coding accuracy and reduce claim deductions, mitigating financial risk. Accelerating EMR adoption is recommended to strengthen hospital claim performance in the national health insurance system. Keyword: Electronic medical record; Diagnosis; Procedure; Hospital revenue; INA-CBGs